Directing the H2-driven selective regeneration of NADH via Sn-doped Pt/SiO2. Issue 4 (3rd February 2022) - Burnett, Joseph W. H.; Li, Jianwei; McCue, Alan J.; Kechagiopoulos, Panagiotis N.; Howe, Russell F.; Wang, Xiaodong
Abstract : High 1, 4-NADH selectivity (90% at full conversion) has been achieved in H2 -driven NAD + reduction using a PtSn/SiO2 bimetallic catalyst, offering a strategy for the development of heterogeneous catalysts for NADH regeneration. Abstract : H2 -Driven NADH regeneration has long suffered from low selectivity when non-enzymatic, particularly heterogeneous catalysts, are used. In addition to the unselective nature of the catalysts, the typically unmeasured NAD + conversion has inevitably hindered catalyst development. Here we report Sn-doped Pt/SiO2 catalysts for the selective regeneration of NADH and show that doping Pt/SiO2 with 10 at% Sn can deliver a selectivity of 90% (at full conversion) using H2 . We propose that this is a result of Sn disturbing the Pt ensemble, altering the mode of NAD + adsorption and directing the reduction to the 1, 4-position of the nicotinamide ring.